Self-regulated and collaborative learning using analog models in digestive system (Praxis Educativa, 2021)
This article aims at evaluating self-regulated and collaborative learning on the digestive system (DS) and homeostasis of the internal environment (IE) using analog models in process in 56 students of the Biological Science Faculty. The students built analogue models reflecting previous and learned ideas about structure-function of DS organs (conduction, secretion, digestion) and integration of molecules to IE. 66% described adequate knowledge about structure-function and continuity of organs; 91% secretion of adnexal glands; 89% digestion and 64% absorption and transport of molecules from DS to IE. Through schemes in process, 100% of students interpreted chemical components in the IE, and 89% classified the types of dehydration, reflecting on possible solutions. In the problem case, 76.5% indicated erroneous previous ideas about IE in the initial scheme, correcting 88% through self-regulated and collaborative learning.
Keywords: Regulated self-learning; Metacognition; learning strategies; Modeling-based learning; Digestive system